Adaptive Dynamic Programming: Single and Multiple Controllers - Song, Ruizhuo; Wei, Qinglai; Li, Qing.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book presents a class of novel optimal control methods and games schemes based on adaptive dynamic programming techniques. For systems with one control input, the ADP-based optimal control is designed for different objectives, while for systems with multi-players, the optimal control inputs are proposed based on games. In order to verify the effectiveness of the proposed methods, the book analyzes the properties of the adaptive dynamic programming methods, including convergence of the iterative value functions and the stability of the system under the iterative control laws. Further, to substantiate the mathematical analysis, it presents various application examples, which provide reference to real-world practices. .
Part I: Preparation -- Introduction to optimal control and adaptive dynamic programming -- Neural networks implementation -- Part II: Optimal control for system with single controller -- Finite-time optimal control -- Multi-objective optimal control -- Multiple actor-critic optimal control via ADP -- Optimal control for complex-valued nonlinear systems -- Chaotic systems optimal tracking control -- Part III: Multi-player systems games -- Optimal control for unknown systems with disturbances -- Zero-sum differential games -- Non-Zero-Sum games -- Synchronization control for multi-agent games.
Keywords: Control engineering; Computational intelligence; Multibody systems; Vibration; Mechanics, Applied; Control and Systems Theory; Computational Intelligence; Multibody Systems and Mechanical Vibrations